THE FACTORS RELATING TO SELF PROTECTION TOOLS ON THE WORKERS (STUDY IN PT. lAPFA COM FEED INDONESIA TBK, THE DIVISION OF TECHNIQUE AND PRODUCTION) IN 2014 - Nita Faradhila Hidayat; Winarko .; Imam Thohari (GEMA LINGKUNGAN KESEHATAN, 2014)
PT. Japfa Comfeed Indonesia Tbk is one of the companies that produce animal feed especiallypoultry feed. Conducive factory environment will optimize operational activities of the company. On thecontrary, inconducive surrounding of the company, where there are lacks of safety, distance to sources ofraw material will induce obstruction to the operation and will create loss to the company. Many workers inPT. Japfa Comfeed Indonesia Tbk who do not wear self protection devices at work, or in the area of thework place. The purpose of this research is to illustrate the factors affecting use of Self Protection devicesat work.This was an observational study. Basedon the time aspect, it was a cross sectional study. Basedon the location this study was classfled as a field research, and considered to be an analytical research tocompare the relationship of variables.Workers who do not wear self Protection devices in PT. Japfa Comfeed Indonesia Tbk of were putunder study and: there were 45,2% workers who do not wear self Protection devices. 40,5% wear itincompletely, and the rest 4,3% wear such devices completely. Results of Chi-Square test indicated thatthere is relationship between knowledge and the use of self protection devices. However, there is norelationship with supervision, training and policy.Workers need to improve their poor habit by complying to the regulation made by the company, orcomply to government polkles which demand workers to wear self protection devices at work. Punishmentshall be given to workers who do not comply to the regulation with regard to the wearing of self protectiondevices at work or in work place area.